Comparative genomics and pangenomics of vancomycin-resistant and susceptible Enterococcus faecium from Irish hospitals. Issue 10 (27th October 2022) - Leigh, Robert J.; McKenna, Chloe; McWade, Robert; Lynch, Breda; Walsh, Fiona
Abstract : Introduction. Enterococcus faecium has emerged as an important nosocomial pathogen, which is increasingly difficult to treat due to the genetic acquisition of vancomycin resistance. Ireland has a recalcitrant vancomycin-resistant bloodstream infection rate compared to other developed countries. Hypothesis/Gap statement. Vancomycin resistance rates persist amongst E. faecium isolates from Irish hospitals. The evolutionary genomics governing these trends have not been fully elucidated. Methodology. A set of 28 vancomycin-resistant isolates was sequenced to construct a dataset alongside 61 other publicly available Irish genomes. This dataset was extensively analysed using in silico methodologies (comparative genomics, pangenomics, phylogenetics, genotypics and comparative functional analyses) to uncover distinct evolutionary, coevolutionary and clinically relevant population trends. Results. These results suggest that a stable (in terms of genome size, GC% and number of genes), yet genetically diverse population (in terms of gene content) of E. faecium persists in Ireland with acquired resistance arising via plasmid acquisition ( vanA ) or, to a lesser extent, chromosomal recombination ( vanB ). Population analysis revealed five clusters with one cluster partitioned into four clades which transcend isolation dates. Pangenomic and recombination analyses revealed an open (whole genome and chromosomal specific) pangenome illustrating a rampant evolutionary pattern. Comparative resistomics and virulomics uncovered distinct chromosomal and mobilomal propensity for multidrug resistance, widespread chromosomal point-mutation-mediated resistance and chromosomally harboured arsenals of virulence factors. Interestingly, a potential difference in biofilm formation strategies was highlighted by coevolutionary analysis, suggesting differential biofilm genotypes between vanA and vanB isolates. Conclusions. These results highlight the evolutionary history of Irish E. faecium isolates and may provide insight into underlying infection dynamics in a clinical setting. Due to the apparent ease of vancomycin resistance acquisition over time, susceptible E. faecium should be concurrently reduced in Irish hospitals to mitigate potential resistant infections.